NUCLEAR MEDICAL CENTRES OF PAEC - Khurshid, S. J. (The Nucleus, 2020)
Pakistan Atomic Energy Commission (PAEC) in the beginning of the 1960’s chalked out plans for the utilization of radiations and radioisotopes for health care of the population and setup two nuclear medical centres at Karachi and Lahore in 1960 and 1963, respectively. Since these centres had only diagnostic facilities, the PAEC later on established eleven more centres in various parts of the country, which have both nuclear medicine and radiotherapy facilities. Initially, the manpower for the medical centres was trained in Europe and America, but later on training facilities were developed within the country at what is now the Pakistan Institute of Engineering and Applied Sciences (PIEAS) which has been organizing M.Sc. level courses in Nuclear Medicine, Medical Physics, and Health Physics. Many of these centres are equipped with modern equipment, which includes single and double head gamma cameras, linear accelerators, Cobolt-60 sources, computerized tomography (CT), magnetic resonance imaging (MRI), brachetherapy, simulators, and treatment planning systems (TPS), mammography, ultrasound and radioimmunoassay (RIA). These tertiary care centres are working in close collaboration with major teaching hospitals and providing diagnostic and treatment facilities to about 350,000 patients annually. PAEC has now also started cancer awareness and screening programme; and has established 13 breast cancer clinics in the medical centres. The public has been informed regarding these facilities through electronic and print media.